COMPUTER GAMES AND THEIR CLASSIFICATION - STOFFOVÁ, Veronika (Trends in education, 2016)
The study deals with computer games and their classification. It analyses their definitions in the information sources, and formulates an own general concise definition. Special attention is paid to didactic computer games and their application in educational processes.
Keywords: computer game; didactic computer game; educational game.